Spatiotemporal expression patterns of wheat amino acid transporters reveal their putative roles in nitrogen transport and responses to abiotic stress - Yongfang Wan; Robert King; Rowan A. C. Mitchell; Keywan Hassani-Pak; Malcolm J. Hawkesford (Scientific Reports, 2017)
Abstract Amino acid transporters have roles in amino acid uptake from soil, long-distance transport, remobilization from vegetative tissues and accumulation in grain. Critically, the majority of wheat grain nitrogen is derived from amino acids remobilized from vegetative organs. However, no systematic analysis of wheat AAT genes has been reported to date. Here, 283 full length wheat AAT genes representing 100 distinct groups of homeologs were identified and curated by selectively consolidating IWGSC CSSv2 and TGACv1 Triticum aestivum genome assemblies and reassembling or mapping of IWGSC CSS chromosome sorted reads to fill any gaps. Gene expression profiling was performed using public RNA-seq data from root, leaf, stem, spike, grain and grain cells (transfer cell (TC), aleurone cell (AL), and starchy endosperm (SE)). AATs highly expressed in roots are good candidates for amino acid uptake from soil whilst AATs highly expressed in senescing leaves and stems may be involved in translocation to grain. AATs in TC (TaAAP2 and TaAAP19) and SE (TaAAP13) may play important roles in determining grain protein content and grain yield. The expression levels of AAT homeologs showed unequal contributions in response to abiotic stresses and development, which may aid wheat adaptation to a wide range of environments.